Strategi Pengembangan Wisata Kuliner Olahan Beras di Desa Wisata Sidan - Widiantara, I Gusti Lanang; Dwi Susanti, Ida Ayu Made; Budiasa, I Made; Listihani, Listihani (Jurnal MeA (Media Agribisnis), 2024)
Organic products are products (plant/livestock products that are produced through practices that are ecologically, socio-economically sustainable, and of good quality (nutritional value and safety against toxins are guaranteed). Organic rice for milk in the Tourism Village has an organic certificate. So, To increase opportunities to introduce organic rice products in the Sidan Tourism Village, innovation is needed in the culinary sector, especially culinary tourism. The aim of this research is to design a strategy based on program objectives through the ISM method in the Sidan Tourism Village. Through ISM analysis, a tourism development strategy can be obtained. culinary processed rice in Sidan Tourism Village.